Physiological and transcriptomic analysis dissects the molecular mechanism governing meat quality during postmortem aging in Hu sheep (Ovis aries) - Li, Huan; Feng, Yan-Hui; Xia, Chao; Chen, Yu; Lu, Xin-Yi; Wei, Yue; Qian, Le-Le; Zhu, Meng-Yao; Gao, Guo-Yv; Meng, Ya-Fei; You, Yv-Le; Tian, Qi; et al. (Frontiers in Nutrition, 2024)
Hu sheep, known for its high quality and productivity, lack fundamental scientific research in China.This study focused on the effects of 24 h postmortem aging on the meat physiological and transcriptomic alteration in Hu sheep. The results showed that the 24 h aging process exerts a substantial influence on the mutton color, texture, and water content as compared to untreated group. Transcriptomic analysis identified 1,668 differentially expressed genes. Functional enrichment analysis highlighted the importance of glycolysis metabolism, protein processing in endoplasmic reticulum, and the FcγR-mediated phagocytosis pathway in mediating meat quality modification following postmortem aging. Furthermore, protein-protein interaction analysis uncovered complex regulatory networks involving glycolysis, the MAPK signaling pathway, protein metabolism, and the immune response. Collectively, these findings offer valuable insights into the molecular mechanisms underlying meat quality changes during postmortem aging in Hu sheep, emphasizing the potential for improving quality control strategies in mutton production.